2010
DOI: 10.1002/jts.20531
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of a reconciliation workshop with and without PTSD psychoeducation in Burundian sample

Abstract: Posttraumatic stress disorder (PTSD) psychoeducation is increasingly offered in diverse cultural settings. As the literature offers theoretical arguments for why such information might be normalizing and distress-reducing, or might risk morbid suggestion of greater vulnerability, a two-sided hypothesis was proposed to examine the specific effect of PTSD psychoeducation. Participants of a trauma healing and reconciliation intervention in Burundi were randomized to conditions with and without PTSD psychoeducatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 27 publications
2
63
0
Order By: Relevance
“…Three examinations into psychoeducation for trauma have concluded that participants showed no improvement or worsening trauma-related problems associated with psychoeducation (Dunn et al, 2007;Niles et al, 2012;Yeomans, Forman, Herbert, & Yuen, 2010) while two studies identified mixed results or only short-term client benefits (Oflaz, Hatipoglu, & Aydin, 2008;Wong, Marshall, & Miles, 2013). In a study comparing a mindfulness-based telehealth intervention to a psychoeducation-based one for combat veterans with PTSD, participants in the mindfulness approach described more satisfaction and more short-term reduction in trauma-related symptoms than the psychoeducation group (Niles et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Three examinations into psychoeducation for trauma have concluded that participants showed no improvement or worsening trauma-related problems associated with psychoeducation (Dunn et al, 2007;Niles et al, 2012;Yeomans, Forman, Herbert, & Yuen, 2010) while two studies identified mixed results or only short-term client benefits (Oflaz, Hatipoglu, & Aydin, 2008;Wong, Marshall, & Miles, 2013). In a study comparing a mindfulness-based telehealth intervention to a psychoeducation-based one for combat veterans with PTSD, participants in the mindfulness approach described more satisfaction and more short-term reduction in trauma-related symptoms than the psychoeducation group (Niles et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study comparing a mindfulness-based telehealth intervention to a psychoeducation-based one for combat veterans with PTSD, participants in the mindfulness approach described more satisfaction and more short-term reduction in trauma-related symptoms than the psychoeducation group (Niles et al, 2012). A randomized trial contrasting recovery workshops for Burundian earthquake survivors found that participants in a workshop without PTSD psychoeducation described greater reductions in PTSD symptoms than those in a workshop that included this training (Yeomans at al., 2010). In another randomized trial which involved 101 male veterans who had chronic combatrelated PTSD and depressive disorders, investigators concluded that participants in the selfmanagement therapy which included psychoeducation showed no clinically significant improvements compared to the control group (Dunn et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Typically, psychoeducation is included at the start of evidence-based treatment protocols such as Exposure Therapy (ET), Eye Movement Desensitization and Reprocessing (EMDR), and cognitive behavioral therapies (Foa et al, 2009). Little research exists on the specific effects of psychoeducation (Ehlers et al, 2003; Yeomans, Forman, Herbert, & Yuen, 2010) to decrease symptoms of PTSD and other common trauma related symptoms.…”
mentioning
confidence: 99%
“…Preliminary studies investigating the specific effects of psychoeducation for reducing distress in trauma-exposed adults (Ehlers et al, 2003; Yeomans et al, 2010) have yielded inconsistent results. One study suggests a single session of psychoeducation may reduce PTSD symptoms (Resnick et al, 2007).…”
mentioning
confidence: 99%
“…However, only a couple of studies have been carried out in recent years; Yeomans and colleagues reported high levels of depression (40 %) and anxiety (61 %) among community adults (Yeomans et al 2008) and internally displaced (Yeomans et al 2010) Burundians. These results highlight the persisting mental health needs of the population, and call for more efforts towards the delivery of mental health interventions in the community.…”
Section: Discussionmentioning
confidence: 99%